TINGKAT KEPUASAN NASABAH TERHADAP PELAYANAN KARYAWAN DI BANK MANDIRI CABANG KOLAKA - Aedil Febri Swarna; Muhammad Askari Zakariah; Nur Hidaya; Hasnah Hasnah; Jumadial Jumadial; Arham Mukkarram (Jurnal Ekonomi Bisnis Syariah, 2018)
The purpose of this study was to determine the level of customer satisfaction towards services in Mandiri Bank Branch Kolaka, as well as knowing how the correlation and regression of each variable of service quality on customer satisfaction by Likert Method. Tests were Carried out, covering Validity and reliability then continued with, test multiple regression analysis using SPSS version 16.0. The results showed that the constant value is -0.027, 0.992 tangiabel, reliability 1.209, 1.433 responsiveness, assurance 1.070 and 0.300 products is not significant. It can be concluded that tangiable, reliability, responsiveness, assurance positively affect customer satisfaction significantly, but not a significant variable affecting product.